The mountain and the feline. A case of group unity in Andean and Amazonian mythology - Rojas Zolezzi, Enrique (2018)
This article is a comparison between the representations of the quechua peasents of the central Andes and the preandean arawak ashaninka as well as other peoples of lowland south america like the desana tukano about sacred mountains and their relations with preys and the felines of the region seen as their guardians.